Reduced Precision Underwrites Ego Dissolution and Therapeutic Outcomes Under Psychedelics - Stoliker, Devon; Egan, Gary F.; Razi, Adeel (Frontiers in Neuroscience, 2022)
Evidence suggests classic psychedelics reduce the precision of belief updating and enable access to a range of alternate hypotheses that underwrite how we make sense of the world. This process, in the higher cortices, has been postulated to explain the therapeutic efficacy of psychedelics for the treatment of internalising disorders. We argue reduced precision also underpins change to consciousness, known as ‘ego dissolution’, and that alterations to consciousness and attention under psychedelics have a common mechanism of reduced precision of Bayesian belief updating. Evidence connecting the role of serotonergic receptors to large-scale connectivity changes in the cortex suggests the precision of Bayesian belief updating may be a mechanism to modify and investigate consciousness and attention.